PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE PADA MATA PELAJARAN IPA KELAS IV (INSTRUKTUR INSTRUKTUR: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Improving student learning outcomes is an essential aspect of educational development. One effective way to enhance learning outcomes is through the use of appropriate teaching models. The Example Non Example model can help students gain a deeper understanding of the material and improve their learning performance. However, the application of this model at the elementary school level is still infrequent and not optimally utilized. This study aims to evaluate the effectiveness of the Example Non Example model in improving student learning outcomes in grade IV science classes. This research is a Classroom Action Research (CAR) conducted in two cycles during February–March 2023 at SDN Cianten 01. Data collection techniques included student learning tests, interviews, documentation, and teacher activity observations. The data were analyzed through assessments of cognitive, affective, and psychomotor domains, as well as teacher activity evaluations. The findings showed that initially, only 32% of the 37 students achieved scores above the Minimum Completeness Criteria (KKM). In the first meeting of cycle I, 35% of students achieved KKM, and in the second meeting, this increased to 69%. In cycle II, 91% of students scored above KKM. The application of the Example Non Example teaching model proved to be effective in improving student learning outcomes in grade IV science. This highlights the importance of selecting appropriate teaching methods to achieve optimal learning results